Lifestyle Factors and Non-Pharmacological Interventions in Mild Cognitive Impairment: Implications for Cognitive Health - Kubiś, Natalia Marianna; Palacz, Bartosz; Teper , Maria Magdalena; Perz , Wiktor; Polus , Aleksander; Wrona , Julia Anna; Gluzicka , Anna; Olczyk , Liwia; Piotrowski , Jędrzej; Korolchuk , Anhelina (Quality in Sport, 2026)
Background. Mild Cognitive Impairment (MCI) is a heterogeneous clinical syndrome associated with an increased risk of progression to dementia, although individual trajectories vary substantially. Growing evidence indicates that modifiable vascular-metabolic, lifestyle, nutritional, and psychosocial factors influence cognitive outcomes in MCI, and that non-pharmacological interventions (NPIs) may support cognitive performance. Aim. To synthesize current evidence on modifiable risk factors associated with progression from MCI to dementia and to evaluate the effectiveness of NPIs targeting cognitive outcomes in patients with MCI. Material and methods. This structured narrative review was based on a targeted search of the PubMed database. Systematic reviews, meta-analyses, longitudinal cohort studies, and randomized controlled trials examining modifiable risk factors and NPIs in MCI were included. Twenty-eight peer-reviewed articles met predefined eligibility criteria and were synthesized narratively. Results. Cardiometabolic conditions, physical inactivity, depressive symptoms, and suboptimal dietary patterns were consistently associated with increased risk of cognitive decline in MCI. Biomarker-informed studies suggest that modifiable factors remain relevant even in patients with underlying Alzheimer’s disease (AD) pathology. Randomized trials and systematic reviews indicate that structured exercise, cognitive training, dietary interventions, and multidomain lifestyle programs are associated with improved cognitive performance, with evidence of dose–response effects. Conclusions. An integrated clinical approach combining assessment of modifiable risk factors with targeted NPIs may support cognitive outcomes in patients with MCI and represents a relevant strategy for early preventive care.